“Multiple intelligences” girl looking for “cooperative learning” boy (Journal of Parents and Teachers, 2013)
The author in this article wants to emphasize the coexistence of two theories that imply two ways of understanding teaching: multiple intelligences and cooperative learning. Both theories have a lot to do with programs and methodology these days. After explaining both theories briefly, the author comes to the conclusion that it is good to combine them and get the best of the students.
Keywords: Multiple intelligences; cooperative learning; didactics; education.